Sexism and sex-role stereotyping in primetime TV advertising - Abayan, Haydee M.
"This study on sexism and sex-role stereotyping in primetime television advertising aim to determine the factors that promote sexism and sex-role stereotyping in primetime television advertising, and in so doing, determine if sexism and sex-role stereotyping in primetime television advertising exists, and if it does, to what extent. All advertisements that appeared from 7:00 p.m to 9:00 p.m in all channels during the period under study, were tabulated regardless of repetition. However, only ads with women and men characters were content analyzed. Each advertisement was measured according to the number of men and women characters, the occupational roles of the characters, the image projected by the characters, the social class of the characters, the setting, the gender of the off-camera voice-over, omissions, word usage, physical exploitation, message of the ad, the dialogue, and the target audience of the ad according to gender. A total of 185 advertisements were analyzed. This study revealed that although most of the ads in primetime TV cater to the women audience, there were more men characters used in the ads. Data showed that sex-role stereotyping is very much against the women. Stereotyping is most promoted by the occupational roles women and men frequently portray, the images which these characters project, the settings where men and women characters are most frequently seen and the concerns of women and men as suggested by the message of every advertisement. Sexism, however, occured at a very minimal level. Defining which is the weaker sex is not important as emphasizing the sexuality of both women and men. The results of this study reveal that advertisers have already began to acknowledge the changing role of women in society, in the sense that ads used women characters with various roles. However, advertisers have yet to implement these changes in terms of portraying women with more varied concerns than beauty and home. The findings of the study show that women are dominantly portrayed as mothers or wives and as girlfriends while men were portrayed with a wider variety of roles. Both men and women characters in the ads were projected with images that epitomize the spirit of the youth. this proves that the advertising industry is putting a big emphasis on the youth segment of the market. Another factor discovered by this study which supports the finding that the advertising industry indeed emphasizes the youth is the setting of the ads. Both men and women characters were most frequently set in outdoor settings. Both men and women characters were also typified as belonging to the middle social class. It is the researcher's recommendation that a similar study be done in later years to determine how the advertisers are implementing into their advertising strategies the various changes that are shaping the new society, which involves mostly, the changing roles and concerns of the women populace."